Asymptotic Tracking Position Control for Nonlinear Systems using BacksteppingTechnique - Md Rozali, Sahazati; Kamarudin, Muhammad Nizam; Rahmat, Mohd Fua'ad; Husain, Abdul Rashid (Elsevier, 2013)
Backstepping is a technique developed for designing stabilizing controls for a special class of nonlinear dynamical systems. It is built from subsystems that radiate out from an irreducible system which can be stabilized using some other method. This method is based directly on the mathematical model of the examined system. It is developed by introducing new variables into it in a form depending on the state variables, controlling parameters and stabilizing functions. The stabilizing functions compensate for nonlinearities exists in the system which affect the stability of its operation. Backstepping can be used for tracking and regulation problem. With the aid of Lyapunov stability design, this paper presents control approach for asymptotical tracking. Electrohydraulic actuator system is chosen as numerical example for the designed controller. The performance of backstepping controller is then compared with unity feedback controller applied to the same system. The results show that backstepping controller produced better output tracking then unity feedback controller.